Pengaruh Pendapatan, Pengetahuan Dan Religiusitas Terhadap Minat Berwakaf Uang Di Kabupaten Sidoarjo - Amansyah, Rizka Apta Liani; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2022)
Waqf is a form of giving up part of the property that is used for the benefit of the welfare of the community. Sidoarjo Regency has great potential for waqf, but in fact waqf in Sidoarjo Regency is only collected a little, this is due to the low public interest in waqf. The low interest in cash waqf occurs due to several influencing factors such as income factors, knowledge factors and religiosity factors. This study aims to determine whether the income factor, knowledge factor and religiosity factor affect a person's interest in cash waqf in Sidoarjo Regency. The method used in this research is quantitative with a questionnaire method with data processing using SPSS. The results of this study indicate that the income factor does not affect the interest in cash waqf in Sidoarjo Regency, while the knowledge factor and religiosity factor affect the interest in cash waqf in Sidoarjo Regency.